2009
DOI: 10.1038/nrn2603
|View full text |Cite
|
Sign up to set email alerts
|

A little more conversation, a little less action — candidate roles for the motor cortex in speech perception

Abstract: The motor theory of speech perception assumes that activation of the motor system is essential in the perception of speech. However, deficits in speech perception and comprehension do not arise from damage that is restricted to the motor cortex, few functional imaging studies reveal activity in motor cortex during speech perception, and the motor cortex is strongly activated by many different sound categories. Here, we evaluate alternative roles for the motor cortex in spoken communication and suggest a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
225
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(242 citation statements)
references
References 96 publications
(175 reference statements)
14
225
2
1
Order By: Relevance
“…It has been suggested that one of the functions of motor activation is tracking the talker's speed and rhythm over time, and provides the timing signals to the auditory cortex. Particularly in a conversation, the monitoring role of the motor system in interacting with the auditory system over time can induce fl uent conversation [53] .…”
Section: Conditionsmentioning
confidence: 99%
“…It has been suggested that one of the functions of motor activation is tracking the talker's speed and rhythm over time, and provides the timing signals to the auditory cortex. Particularly in a conversation, the monitoring role of the motor system in interacting with the auditory system over time can induce fl uent conversation [53] .…”
Section: Conditionsmentioning
confidence: 99%
“…Finally, recent work using repetitive TMS has revealed that disruption to regions of the premotor cortex impacts on perceptual discrimination of speech sounds (5) in a somatotopic manner (6). These studies are all consistent with the proposal that the motor system is activated (and perhaps even essential) in the perception of speech.However, although there is agreement that motor regions can be activated in speech perception studies, recent reviews of the literature have raised two important challenges over precisely what drives this activation (7,8). The first challenge stems from the fact that neuroimaging data have been inconsistent, with relatively few studies showing motor activity at a whole-brain corrected level of significance compared with matched nonspeech conditions (7).…”
mentioning
confidence: 99%
“…However, although there is agreement that motor regions can be activated in speech perception studies, recent reviews of the literature have raised two important challenges over precisely what drives this activation (7,8). The first challenge stems from the fact that neuroimaging data have been inconsistent, with relatively few studies showing motor activity at a whole-brain corrected level of significance compared with matched nonspeech conditions (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations